Kewarisan Bilateral Suku Jawa di Dusun VII Sei. Cabang Kiri Sumatera Utara Perspektif Maqashid Syari’ah - Eva, Yusnita; Fitri, Desi Widya (Institut Agama Islam Negeri Kerinci, 2024)
The bilateral inheritance system ensures equal rights for men and women while reflecting social justice values rooted in local traditions. However, its practice often sparks debates regarding its alignment with Islamic law. This study aims to analyze the practice of bilateral inheritance in the Dusun VII Sei. Cabang Kiri community, Langkat Regency, through the lens of maqashid syariah, focusing on equity and public benefit. Employing a semi-ethnographic design with a qualitative approach, the research involved structured interviews and thematic data analysis to understand inheritance patterns and their underlying values. The findings reveal that the bilateral inheritance system in this community aligns with the principles of maqashid syariah through family deliberation (musyawarah), fostering justice, equality, and social harmony. Such a system not only exemplifies the integration of local customary values and maqashid syariah but also serves as a relevant model for achieving justice, equality, and social harmony within Indonesia’s pluralistic legal framework. Future research is recommended to adopt comparative or interdisciplinary approaches to further explore similar practices in other indigenous communities across Indonesia.